2007
DOI: 10.1016/j.chroma.2007.07.078
|View full text |Cite
|
Sign up to set email alerts
|

Could linear solvation energy relationships give insights into chiral recognition mechanisms?

Abstract: Five parameter linear solvation energy relationships (LSER) are known to have little or no shape recognition ability. However, it is proposed to use LSER studies to get insights into chiral recognition mechanisms. Since the two enantiomers have exactly the same five A-V solute descriptors being still separated by chiral stationary phases (CSPs), it can be considered that they form two different transient diastereoisomers with the CSP. It is then possible to perform LSER studies on the enantioselectivity factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…The v coefficient describing dispersion interactions represents the most important interaction that leads to decrease of retention in both separation systems. Negative values of the term v are typical for a normal phase mode . Higher absolute values of the v coefficient in SFC indicates that the mobile phase participates in dispersion interactions with the solute to a greater extent in SFC than in HPLC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The v coefficient describing dispersion interactions represents the most important interaction that leads to decrease of retention in both separation systems. Negative values of the term v are typical for a normal phase mode . Higher absolute values of the v coefficient in SFC indicates that the mobile phase participates in dispersion interactions with the solute to a greater extent in SFC than in HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…The linear free energy relationship model (LFER) is an effective tool for qualitative and quantitative characterization of interactions participating in the retention mechanism (e.g. ). However, it must be understood that not all interactions that lead to retention can lead to chiral recognition.…”
Section: Introductionmentioning
confidence: 99%
“…To define the groups of solutes sharing a common enantiorecognition mechanism, we adopted a procedure first suggested by Mitchell et al [12], who investigated chiral recognition mechanisms on macrocyclic glycopeptide CSPs using HPLC. Our study used a much larger number of racemates so that the conclusion based on a better data set would be more substantiated.…”
Section: Factorial Discriminant Analysis Based On Three Classes: Defimentioning
confidence: 99%
“…Recent studies of Mitchell et al [12,13] showed that the solvation parameter model [14] can provide relevant information about the interactions contributing to retention and enantioselective separation on different macrocyclic glycopeptide and immobilized polysaccharide-based CSPs in HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…polysaccharide-based CSPs, [2][3][4][5][6][7][8][9][10][11] macrocyclic antibiotic CSPs, [12][13][14][15][16][17][18][19][20][21][22] and π complex CSPs. [23][24][25][26] Researchers continue to make great efforts to develop new HPLC CSPs, which could make a substantial impact on enantiomeric separations.…”
mentioning
confidence: 99%